2017
DOI: 10.1016/j.celrep.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Targeting of S6K1 in PTEN-Deficient Neoplasia

Abstract: SUMMARY Genetic S6K1 inactivation can induce apoptosis in PTEN-deficient cells. We analyzed the therapeutic potential of S6K1 inhibitors in PTEN-deficient T cell leukemia and glioblastoma. Results revealed that the S6K1 inhibitor LY-2779964 was relatively ineffective as a single agent, while S6K1-targeting AD80 induced cytotoxicity selectively in PTEN-deficient cells. In vivo, AD80 rescued 50% of mice transplanted with PTEN-deficient leukemia cells. Cells surviving LY-2779964 treatment exhibited inhibitor-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
5
15
0
Order By: Relevance
“…However, RET is neither mutated nor expressed in the cancer cell lines used in our study based on published data (37,38). More recently, AD80 has been demonstrated as highly active in lung cancer models containing Kif5B-Ret fusions (39) and also in PTEN-deficient malignancies (40). Our study is the first to demonstrate high activity of AD80 in liver cancer models.…”
Section: Ad80 Induces Transcriptomic Reprograming To a Less Aggressivsupporting
confidence: 56%
“…However, RET is neither mutated nor expressed in the cancer cell lines used in our study based on published data (37,38). More recently, AD80 has been demonstrated as highly active in lung cancer models containing Kif5B-Ret fusions (39) and also in PTEN-deficient malignancies (40). Our study is the first to demonstrate high activity of AD80 in liver cancer models.…”
Section: Ad80 Induces Transcriptomic Reprograming To a Less Aggressivsupporting
confidence: 56%
“…Further analysis revealed that sfRon induces AKT-mTORC1-S6K1-S6 signaling, including S6K1 downstream targets such as ribosomal protein S6 and eukaryotic initiation factor 4B (eIF-4B) ( Figure 1B). Previous reports show that S6K1 is a hub for translation control that regulates protein synthesis in dividing cells and enhances cell proliferation [19,20]. In agreement with these findings, we found that sfRon expressing cell lines and PDXs exhibited increased levels of proliferation marker PCNA ( Figure 1B).…”
Section: The Sfron Expression Is Associated With High Activity Of Thesupporting
confidence: 91%
“…Further studies showed that the S6K1 phosphorylation was not accompanied by the increase in phosphorylation of the mTORC1 substrate 4E-BP1 ( Figure 3E). The S6K1 T389 phosphorylation without concomitant activation of mTORC1 downstream targets has been previously describe with other S6K1 inhibitors [20]. However, after drug(s) removal from cells (washout), the cells treated with BMS777607 or BKM120 resumed their signaling to certain extend, while cells treated with AD80 or AD80+BMS777607 had their target-specific signaling completely suppressed ( Figure 3E and Supplementary Table 1).…”
Section: Treatment With Multi-kinase Inhibitor Ad80 Alone or In Combisupporting
confidence: 72%
“…These data also provide important insights into the crosstalk between the mTOR/S6K1 signaling pathway and Myc activation. Several S6K1 inhibitors, such as PF-4708671, LY-2779964 and AD80, have been suggested to be effective in some advanced cancers 52 , 53 . In particular, the compound LY-2779964 has undergone a phase I clinical trial in patients with advanced cancers 54 .…”
Section: Discussionmentioning
confidence: 99%